REFERENCE PRICE, PRICE PERCEPTION AND WILLINGNESS TO PAY (Journal of Media studies, 2020)
The product price plays a strategical role for bothorganizations, in terms of profitability and consumer lives in terms of utilitymaximizing. However, it is difficult to predict consumer behavior towardestablished prices by firms. The research works predict that consumer priceperception and willingness to pay are different. Also, a consequence of price hasbeen analyzed under three theories (1) Adaptation theory (2) assimilation theoryand (3) transaction utility theory. In addition to that, this work shows five typesof price perception (positive and negative price perceptions) and consumermodel of willingness to pay.